2020
DOI: 10.3390/nu13010043
|View full text |Cite
|
Sign up to set email alerts
|

Undernutrition and Obesity Are Associated with Adverse Clinical Outcomes in Hospitalized Children and Adolescents with Acute Pancreatitis

Abstract: Background: Adult studies demonstrated that extremes of nutritional status adversely impact clinical outcomes in acute pancreatitis (AP). With rising prevalence of undernutrition/obesity in children, we analyzed the effect of nutritional status on the clinical outcomes in children and adolescents with acute pancreatitis. Methodology: We analyzed the Kids’ Inpatient Database (KID) between 2003 and 2016 to include all patients with a primary diagnosis of AP using specific International Classification of Diseases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…In a single-center retrospective study by Vasilescu et al [12] showed that malnutrition was significantly associated with prolonged length of hospital stay (16.5 days) when compared to 10.6 days (normal weight) and 10.7 days (obesity). Thavamani et al [13] also showed similar findings using the Kids' Inpatient Database. This study showed that undernutrition was associated with an increased length of hospital stay of an additional 6 days with an additional $16,000 in hospitalization cost [13].…”
Section: Nutritional-related Risk Factors For Acute Pancreatitismentioning
confidence: 60%
See 1 more Smart Citation
“…In a single-center retrospective study by Vasilescu et al [12] showed that malnutrition was significantly associated with prolonged length of hospital stay (16.5 days) when compared to 10.6 days (normal weight) and 10.7 days (obesity). Thavamani et al [13] also showed similar findings using the Kids' Inpatient Database. This study showed that undernutrition was associated with an increased length of hospital stay of an additional 6 days with an additional $16,000 in hospitalization cost [13].…”
Section: Nutritional-related Risk Factors For Acute Pancreatitismentioning
confidence: 60%
“…Thavamani et al [13] also showed similar findings using the Kids' Inpatient Database. This study showed that undernutrition was associated with an increased length of hospital stay of an additional 6 days with an additional $16,000 in hospitalization cost [13]. This study also showed that both undernutrition and obesity are associated with significantly increased severity of AP of 2.5 times and 1.6 times for undernutrition and obesity respectively.…”
Section: Nutritional-related Risk Factors For Acute Pancreatitismentioning
confidence: 60%
“…Disease severity classifications were determined in 2017 by an expert panel and are determined by the presence or absence of local complications, transient (<48 h), or prolonged organ failure (>48 h) [36]. Recent studies suggest that undernutrition, obesity, and trauma or drug-induced risk factors are associated with more severity [8,38,39,40 ]. Much effort has been made to determine risk stratification tools [41][42][43]; however, efforts have previously been limited by prior lack of consensus severity classifications or inability to validate across different populations [36].…”
Section: Complicationsmentioning
confidence: 99%
“…Disease severity classifications were determined in 2017 by an expert panel and are determined by the presence or absence of local complications, transient (<48 h), or prolonged organ failure (>48 h) [36]. Recent studies suggest that undernutrition, obesity, and trauma or drug-induced risk factors are associated with more severity [8,38,39,40 ▪ ].…”
Section: Complicationsmentioning
confidence: 99%
“…The death rate of SAP is as high as 15%-35% [1], posing a serious threat to population health. According to clinical studies, obesity, as an independent risk factor for the development of AP could increase AP morbidity and mortality [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%